Chinese Flower and Bird Painting: A New Form of Art Therapy for Depression - Biyun Zhang; Jingyao Chen; Xiaoyan Huang; Wenhao Xu (SAGE Open, 2021)
Depression is a complex psychological disorder. Although psychological counseling and traditional Western art therapy have obtained robust results in the diagnosis and treatment of depression, they are not well accepted in China due to cultural differences. Chinese flower and bird painting has been favored in China and beyond. It is of considerable significance to studying the auxiliary treatment of depression by using Chinese flower and bird painting. First of all, during observation of the painting style and works of patients with different severities of depression, such phenomena as broken strokes, roughness at the end of the painting brush, stroke discontinuity, and uneven breath are noted. These signs reflect impatience and lack of control in patients with depression. Subsequently, a three-stage Chinese flower and bird painting art therapy intervention focusing on breathing training to improve ink brush control is established, and this adjuvant art therapy was applied to 56 people with mild and moderate depression. Experimental results show that, via a 24-week Chinese flower and bird painting art therapy intervention, the observation group has a greater decline in Hamilton Rating Scale for Depression (HAMD) scores than the control group ( p < .05). The study on electroencephalogram (EEG) shows that The normal rate of brain waves of the observation group in the middle and late stages of treatment and after treatment is 73%, significantly higher than 32% in the control group. This research shows that Chinese flower and bird painting can be used as a new and effective adjuvant treatment for depression in line with Chinese characteristics and is worthy of in-depth research.